Progress, Challenges, and Sustainable Perspectives in Nuclear Energy Strategies - Pablo Fernández-Arias; Georgios Lampropoulos; Álvaro Antón-Sancho; Diego Vergara (Applied Sciences)
This bibliometric review of global nuclear energy strategies reveals a renewed interest in this technology as a fundamental part of the energy transition and the fight against climate change. The findings highlight an emerging leadership of China and other Asian countries in scientific production, although the United States and European countries maintain a greater impact in their research. There is an evolution from a purely technical focus to a greater focus on security, energy policy, climate change, and sustainability, reflecting a more holistic understanding of the role of nuclear energy. The 21st century has seen a resurgence of interest in nuclear energy, driven by concerns about climate change, although these topics are still relatively underrepresented in specialized literature. New areas of research are identified, such as integration with renewable energy and advanced applications. Research on public perception and social acceptance has gained sophistication. Surprisingly, an apparent lack of scientific interest in international collaboration is detected, despite its recognized importance in addressing global challenges and promoting the peaceful use of nuclear energy. This analysis provides a comprehensive overview of the current status and future trends in nuclear energy research and strategies.